Exploring EFL Students’ English Reading Habits: Reading beyond Classroom Practice - Nafilatul Janah, Karunia Eka; Latief, Mohammad Adnan; Andreani, Sri (JET ADI BUANA, 2021)
Some previous studies have proven that having good reading habits is important for students. Regarding the importance of having good reading habits, it is essential that students who learn English as Foreign Language (EFL) to develop good English reading habits. If EFL students have good English reading habits, it will be much easier for them to receive language inputs and produce some language outputs after reading. The study is intended to investigate whether EFL students have good English reading habits as the fact that it is important for EFL students to develop good English reading habits. It covers the students’ general attitudes toward reading, the students’ amount of practice for reading English books, types of English materials the students read, topics of English texts the students read, number of English books the students read, the students’ purposes in reading English materials, and the students’ beliefs of English reading habits. This study uses descriptive research survey involving 154 EFL students of a state university in Malang, East Java, Indonesia. The results show that EFL students have developed good English reading habits, but they still need improvement in the frequency of reading practice and the number of books read. Besides, they have positive attitudes toward reading, various kinds of English reading texts and topics to read, various reading purposes, and positive beliefs toward English reading habits. However, it is found that some respondents have difficulties to give fast responses in answering the questions through the questionnaire platform used. Therefore, some suggestions are also given as the recommendations for future researchers related to this field of study.